2000
DOI: 10.1016/s0032-0633(00)00016-7
|View full text |Cite
|
Sign up to set email alerts
|

Penetration tests on the DS-2 Mars microprobes: penetration depth and impact accelerometry

Abstract: We describe the results of three separate sets of impact tests conducted during the development of the DS-2 Mars Microprobe mission. As well as indicating the promise of penetration to H0.5 m depth on Mars, these tests show the utility of accelerometer data in determining the penetration depth, the hardness of the surface material and the existence of layers, and the presence of coarse-grained material. Various lessons learned in instrumentation and operation, airgun testing and target characterization, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 13 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…This gun has been used more recently in penetration tests of DS-2 forebodies [3] , and in studies of impact heating and triboelectric charging [4]. This facility was used in the nose-shape optimization trials, but was both too narrow for the coring penetrator and too short to accelerate the larger mass at acceptably low chamber pressures, the tank on the original gun being rated to only about 5 bar.…”
Section: Air Gunmentioning
confidence: 99%
See 2 more Smart Citations
“…This gun has been used more recently in penetration tests of DS-2 forebodies [3] , and in studies of impact heating and triboelectric charging [4]. This facility was used in the nose-shape optimization trials, but was both too narrow for the coring penetrator and too short to accelerate the larger mass at acceptably low chamber pressures, the tank on the original gun being rated to only about 5 bar.…”
Section: Air Gunmentioning
confidence: 99%
“…Density was determined simply by weighing just prior to target installation, the volume of the target being known as the rigid container was filled to a consistent depth. The bulk density of the target material was determined to be between 550 and 750 kg/m 3 At the low temperatures of these tests, a shear vane gauge (where a cruciform vane is rotated to determine shear strength) had insufficient range to capture a strength measurement.…”
Section: Target Documentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine structure in the accelerometer record may indicate structure at the centimeter level. Laboratory tests [Lorenz et al, 1999b] indicate that a high-frequency noise component is found in coarse gravel targets that is not present in finer-grained materials. Another observation that has been made in these tests is that paint applied to the forebody is, in general, only abraded away on the hemispherical nose.…”
Section: Polar Layered Terrain and The Ds2 Test Programmentioning
confidence: 99%
“…For these proof-of-concept experiments, two test articles were constructed, using 40mm diameter penetrator forebodies developed 3 years previously for impact tests of the DS-2 Mars penetrators [5,6,7]. All the bodies had been machined from brass.…”
Section: Proof-of-conceptmentioning
confidence: 99%